Up to 12 Months of Elagolix Sustained Menstrual Blood Loss Reduction in Women With Uterine Fibroids [OP04-5D]. (May 2020) - Simon, James A.; Bradley, Linda D.; Liu, Ran; Owens, Charlotte; Schlaff, William
Abstract : INTRODUCTION: An investigational, IRB-approved, phase 3 extension study (Elaris UF-EXTEND) of two 6-month, phase 3 studies evaluated the efficacy and safety of an additional 6-months (up to 12-months) of elagolix (oral gonadotropin-releasing hormone antagonist) with hormonal add-back therapy in women with heavy menstrual bleeding (HMB) and uterine fibroids (UF). METHODS: Women who received elagolix 300 mg twice-daily with add-back (estradiol 1 mg/norethindrone acetate 0.5 mg once-daily [E2/NETA]) or elagolix alone in the preceding studies continued the same treatment for an additional 6-months in the extension study. Primary endpoint was the percentage of women with menstrual blood loss (MBL) <80 mL during final month of treatment and ≥50% MBL reduction from baseline to final month of treatment; MBL measured by alkaline hematin method. Safety assessments included bone mineral density (BMD) changes. RESULTS: 433 women who completed the 6-month treatment period in either of the two preceding studies were enrolled in the extension study. In women who received up to 12-months of elagolix+E2/NETA, 87.9% met the primary endpoint; 74.8% had suppression of bleeding (no bleeding, spotting allowed) at final month; 72.5% with baseline hemoglobin ⩽10.5g/dL had an hemoglobin increase >2 g/dL at extension month 6. Mean baseline MBL (mean±SD=224.7±147.9 mL) was reduced with elagolix+E2/NETA as early as extension month 1 (mean [95% CI]=-186.5 [-209.2, -163.9] mL) and sustained through extension month 6 (mean [95% CI]=-221.4 [-239.11, -183.68] mL). Mean BMD decreases from baseline to extension month 6 were significantly less with elagolix+E2/NETA than elagolix alone. CONCLUSION: Up to 12-months of elagolix+E2/NETA provided sustained MBL reduction in women with UF. Inclusion of add-back attenuated BMD decreases associated with elagolix alone.